Cohesiveness of social and individual forces in strengthening attitude-pro-environment behaviour relationship – a concept paper - Yoong, Siew Wai; Bojei, Jamil (2015)
Urbanisation, population growth and increasing affluence have had a significant impact towards climate changes and environmental challenges. Generally speaking, there is a reversed relationship between the advancement in human development and the state of the environment. The world shares similar concerns and worries pertaining to the environmental changes, and various initiatives, legislative framework, reward mechanisms and investments have taken place to combat and address the immense environmental consequences. However, the return of the effort is unsatisfactory, judging from the upward trend of greenhouse gas emission, exhausted natural resources, biodiversity loss and natural disasters. Initiatives at the macro level lack the magnetic effects and disconnect from the grassroots and masses. This study is therefore to extend existing body of knowledge in understanding the nexus of pro-environment behaviours adoption from following perspectives (a) Individual engagement with society based on pro-environmental activities for fulfilling social needs, where the social activities will enable one to enjoy the social gathering by interacting with other members; (b) Empowerment and efficiency in realizing desired collective benefit through an ethical community as compared to acting individually. Moreover, collective action is able to ensure transparency, authenticity and reliability as the community is operated systematically; and (c) Diffusion of sustainable behaviour through interaction, knowledge and experience sharing among members. Ethical community serves as a platform for members to sought guidance when they are trapped in ethical dilemma. This paper is aimed at facilitating subsequent strategic action plans development from policy makers and marketers, to strengthen links between producers and environmental-conscious users, which subsequently cultivate environmental-friendly lifestyle.